Liquor Flavour Is Associated With the Physicochemical Property and Microbial Diversity of Fermented Grains in Waxy and Non-waxy Sorghum (Sorghum bicolor) During Fermentation - Liu, Chunjuan; Gong, Xiangwei; Zhao, Guan; Soe Htet, Maw Ni; Jia, Zhiyong; Yan, Zongke; Liu, Lili; Zhai, Qinghua; Huang, Ting; Deng, Xiping; Feng, Baili (Frontiers in Microbiology, 2021)
The fermentation process of Chinese Xifeng liquor involves numerous microbes. However, the sources of microbes in fermented grain and the link between liquor flavour and physicochemical properties and microbial diversity during fermentation still remain unknown. Herein, two waxy (JiNiang 2 [JN-2] and JinNuo 3 [JN-3]) and four non-waxy (JiZa 127 [JZ-127], JinZa 34 [JZ-34], LiaoZa 19 [LZ-19] and JiaXian [JX]) sorghum varieties were selected for the comprehensive analysis of the relationship between liquor flavour and the physicochemical properties and microbial diversity of fermented grains. Results showed that ethyl acetate was the main flavour component of JZ-127, JZ-34 and JX, whereas ethyl lactate was mainly detected in JN-2, JN-3 and LZ-19. Ethyl lactate accounted for half of the ethyl acetate content, and JX exhibited a higher liquor yield than the other sorghum varieties. The fermented grains of waxy sorghum presented higher temperature and reducing sugar contents but lower moisture and starch contents than their non-waxy counterparts during fermentation. We selected JN-3 and JX sorghum varieties to further investigate the microbial changes in the fermented grains. The bacterial diversity gradually reduced, whereas the fungal diversity showed nearly no change in either JN-3 or JX. Lactobacillus was the most abundant bacterial genus, and its level rapidly increased during fermentation. The abundance of Lactobacillus accounted for the total proportion of bacteria in JX, and it was higher than that in JN-3. Saccharomyces was the most abundant fungal genus in JX, but its abundance accounted for a small proportion of fungi in JN-3. Four esters and five alcohols were significantly positively related to Proteobacteria, Bacteroidetes and Actinobacteria; Alphaproteobacteria, Actinobacteria and Bacteroidia; Bacillales, Bacteroidales and Rhodospirillales; and Acetobacter, Pediococcus and Prevotella_7. This positive relation is in contrast with that observed for Firmicutes, Bacilli, Lactobacillales and Lactobacillus. Meanwhile, Aspergillus was the only fungal microorganism that showed a significantly negative relation with such compounds (except for butanol and isopentanol). These findings will help in understanding the fermentation mechanism and flavour formation of fermented Xifeng liquor.